The Impact of Normative Social Influence on Sustainable Consumption Behavior: The Mediating Role of Eco-Friendly Behavior and Environmental Awareness - Sarıoğlu, Cüneyd İkbal (International Review of Management and Marketing, 2026)
Sustainable consumption has gained importance through social, economic and environmental platforms and social norm communication triggered and empowered eco-environmental behavior. This study aims at investigating the impact of normative social influence on sustainable consumption behavior built on a comprehensive theoretical and practical framework with special reference given to the role of environmental awareness and the eco-friendly behavior. This study investigates the process by which social norms transform into sustainable consumption behavior by carefully selecting relevant scales within the Turkish context. 1418 participants completed the questionnaire online. The study concluded that the effect of normative social influence on sustainable consumption behavior (H1) and the effect of normative social influence on environmentally friendly behaviors (H2) was found to be positive and significant. However, it was found that the effect of normative social influence on environmental awareness was not statistically significant (H3). The study revealed that environmentally friendly behaviors (H4) and that environmental awareness has a positive and significant effect on sustainable consumer behavior (H5). It is also found that environmentally friendly behaviors mediate the relationship between normative social influence and sustainable consumption behavior (H6). This study is an attempt to provide a solid foundation for investigating the psychological and social drivers of sustainable consumption behavior.